How smartwatch use drives user reciprocity: The mediating effects of self-expansion and self-extension - Liu, Rong; Yang, Jiawei; Yao, Junwen (Frontiers in Psychology, 2022)
People are increasingly using smartwatches in their daily lives. Scholars have focused on the drivers of the initial and continued use of smartwatches, while few studies have dealt with the outcomes of smartwatch use. Therefore, this study explores the impact of smartwatch use on user experience (self-expansion and self-extension) and user reciprocity (user loyalty and user influence) based on service-dominant logic. Data were collected through a questionnaire survey of 343 smartwatch users. Structural equation modeling and the bootstrapping method were applied to test the theoretical hypotheses. The results show that smartwatch use positively affects self-expansion and self-extension, both self-expansion and self-extension positively affect user loyalty and user influence, and smartwatch use affects user loyalty and user influence through self-expansion and self-extension. This research deepens our understanding of the outcomes of smartwatch use, and provides insights for smartwatch manufacturers to create more value from user reciprocity.